Survey Research Trends on English Language Teaching in Indonesia: Compare to Mathematics Teaching - Khairul Azmi Siagian (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2023)
The study aimed to investigate the trends of survey research on English Language Teaching (ELT) in the Indonesian context between 2015 and 2022, including topics, samples, level of education, and locations where the previous studies were conducted. It also compared the development of the survey research on ELT and Mathematics Teaching (MT). The study used content analysis using the Semantic Scholar database as the data source. The study set some criteria to filter articles collected: (1) Indexed in a reputable journal; (2) Focus on education (ELT/MT); (3) The articles must be between 2015 and 2022; (4) The articles must use survey research design; and (5) Open access journal that has pdf. The results showed that survey research on ELT increased in the Indonesian context between 2015 and 2022. The results showed that survey research on ELT has significantly improved since 2015-2022 than survey research on MT. The most frequent topics examined in the previous study were online learning, need analysis, and attitude and motivation. Further, students became the most popular research sample used in ELT and most frequently conducted at the university level. The majority of previous studies were conducted in Java. This study was expected to help future researchers find research gaps using survey research design